Strategi Guru Dalam Menumbuhkan Keterampilan Berbahasa Indonesia Di Mi Ma’arif Kadipaten - Lisma Meilia Wijayanti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to describe and analyze the strategies implemented by teachers at MI Ma'arif Kadipaten to develop students' Indonesian language skills, including listening, speaking, reading, and writing, within a creative, contextual, and enjoyable learning context. This study used a descriptive qualitative approach to explore teachers' strategies in developing Indonesian language skills at MI Ma'arif Kadipaten. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The analysis was strengthened through triangulation to ensure the data obtained were valid and reflected in the realities of the field. The results indicate that teachers at MI Ma'arif Kadipaten successfully developed students' listening, reading, writing, and speaking skills through creative, enjoyable, and student-centered strategies. Listening and reading instruction was conducted using an approach that addressed cognitive, emotional, and social aspects, and supported by a literacy-rich learning environment. Writing skills were developed through the use of images, daily journals, and literacy activities that foster student expression. Meanwhile, speaking skills are enhanced through storytelling, role-playing, and stage performances, which foster students' courage and confidence.